Stargrass: SS-AGR-62/AG154, rev. 11/2017 - Vendramini, J.; Mislevy, P. (EDIS, 2017)
The purpose of the document is to provide comprehensive information and guidelines on the cultivation, management, and utilization of stargrass (Cynodon spp.), specifically focusing on recommended varieties, growing conditions, cultural practices, and the advantages and disadvantages of stargrass as a forage crop. This detailed resource aims to assist farmers and ranchers in understanding the optimal methods for establishing and managing stargrass to maximize forage production and animal performance in warm-season environments. The document also highlights the specific traits and benefits of various stargrass varieties, offering practical insights into effective fertilization, weed and pest control, grazing management, and hay production strategies. Overall, it serves as a valuable guide for those seeking to incorporate stargrass into their agricultural operations for improved livestock productivity and forage quality. First published in August 2002.